Association of CSR Disclosure with Accounting Conservatism : A Study of Select Indian Mining Firms - Patro, Binoti; Pattanayak, J. K. (Indian Journal of Finance, 2017)
The aim of the present study was to obtain evidence of the influence of corporate social responsibility (CSR) disclosure on accounting conservatism (AC). Measurement of conservatism was done by the use of discretionary accruals. The measurement of CSR reporting is based upon the guidelines issued by the Global Reporting Initiative (GRI), obtaining data from annual reports of different mining firms. The population considered in this study were Indian mining companies enlisted in PROWESS IQ database for the period from 2000-2015. This study used purposive sampling method for data collection for 34 mining companies. The results of this study indicated a significant negative relationship existing between accounting conservatism and CSR disclosure.